MUSIM PEMIJAHAN IKAN PELANGI ARFAK (Melanotaenia arfakensis ALLEN) DI SUNGAI NIMBAI DAN SUNGAI AIMASI, MANOKWARI [Spawning Season of Arfak Rainbowfish (Melanotaenia arfakensis Allen) in Nimbai and Aimasi Streams, Manokwari] - Emmanuel Manangkalangi; M. F. Rahardjo; Djadja S. Sjafei; Sulistiono Sulistiono (Jurnal Iktiologi Indonesia, 2009)
The study was aimed to describe the spawning season of arfak rainbowfish (Melanotaenia arfakensis) in Nimbai and Aimasi streams, both are located in Prafi river system. Sampling was conducted from June to December 2007 and carried out monthly in four different habitat types using hand net. A total of 752 individual specimens were collected and consisted of five developmental stages, namely egg, larvae, juvenile, young and adult. There was no different proportion in both sexes, either habitat type or time. This species has relatively low fecund, producing approximately 23-1,351 eggs with relatively large diameter (0.5-1.3 mm). Large egg diameter was distributed in posterior of ovaries, with 2-3 modes, and presence of atretic eggs, and was indicated as multiple spawner fish. However, based on gonado somatic index, condition factor, presence of eggs and larva in limited period showed that there were increased reproductive activities in both locations from June to September, with low water flow condition. Concentration of reproduction activity during dry season to ensure that larva was produced relatively stable and in benign physical condition. In order to maintain the population of this species, both of these streams should be reserved as their natural habitats, thereby its life cycles could go on.